ADSORPTION OF NICKEL IN NICKEL SULPHATE SOLUTION (NISO4) BY LAPINDO MUD (Universitas Negeri Semarang, 2017)
This research has been carried out to produce adsorbent from Lapindo mud through various activation process, to adsorb nickel from nickel sulfate solution. Several investigations were performed in this research such as characterization of Lapindo mud before and after activation, effect of physical, chemical and chemico-physical activation to Si/Al ratio and determine the most effective method to produce adsorbent with high adsorption rate. Lapindo mud in this research was prepared through several methods such as without activation, calcination at 500 °C for 3 hours, chemical activation with 6 N HCl under reflux for 6 hours, chemical activation with 6 N NaOH under reflux for 6 hours, chemical activation with 6 N HCl under reflux followed by calcination process and the last treatment is chemical activation with 6 N NaOH under reflux followed by calcination process. The object of this research is the Lapindo mud adsorbent ability to adsorb Ni from NiSO4 solution. While activation methods and nickel concentration in this become independent variable. The reduction of nickel concentration efficiency is determined by the nickel concentration before and after adsorption process. The Si/Al ratio of Lapindo mud before activation process was 3.01 and it increase as the mud is activated. The highest Si/Al ratio was found at activation using HCl which is 7.85. Chemical activation using NaOH was found to be the best method to create the adsorbent with adsorption capacity 98.3%.